Signos de resonancia magnética en diagnóstico de hernia discal - Apolo Ordoñez, Fabricio Silverio (Machala : Universidad Técnica de Machala, 2020)
A herniated disc is defined as the displacement caused by pressure from the upper or lower vertebra and results in a detached or ruptured disc, the herniated nucleus pulposus can put pressure on the nerves near the disc, which causes pain. Recurrence of these hernias usually occurs in the lower spine and is one of the most common causes of low back pain or leg pain. OBJECTIVE: To describe the signs of magnetic resonance imaging in the diagnosis of herniated disc through the bibliographic review of scientific articles. METHODOLOGY: A descriptive study was carried out through an exhaustive search of scientific articles that address the radiological signs of herniated disc through databases such as PUBMED, COCHRANE and Google Scholar of the last 5 years. RESULTS: 15 bibliographic reviews were shared describing the imaging characteristics in the diagnosis of herniated disc by magnetic resonance, in addition to the differential diagnosis with other disc pathologies through radiological findings that define and conclude the presence of a herniated disc. CONCLUSION: Magnetic resonance imaging in the diagnosis of herniated disc has superiority over computed tomography and myelography, since it does not use ionizing radiation and is the most specific study to visualize the anatomy of the spine in order to detect injuries, abnormalities or diseases that with other diagnostic methods are not possible to be detected.
Una hernia discal es definida como el desplazamiento originado por una presión de la vértebra superior o inferior y da lugar a un disco desprendido o roto, el nucleus pulposus herniado puedo dar presión a los nervios cercanos al disco, lo que causa dolor. La recurrencia de estas hernias suele ocurrir en la zona inferior de la espina dorsal y es una de las causas más comunes de dolor lumbar o dolor de piernas. OBJETIVO: Describir los signos de resonancia magnética en el diagnóstico de hernia discal mediante la revisión bibliográfica de artículos científicos. METODOLOGÍA: Se realizó un estudio descriptivo mediante una búsqueda exhaustiva de articulos científicos que aborden los signos radiológicos de hernia discal a través de base de datos como PUBMED, COCHRANE y Google Scholar de los últimos 5 años. RESULTADOS: Se comparó 15 revisiones bibliográficas en donde se describen las características imagenológicas en el diagnóstico de hernia discal por resonancia magnética, además del diagnóstico diferencial con otras patologías discales a través de los hallazgos radiológicos que definen y concluyen la presencia de una hernia discal. CONCLUSIÓN: La resonancia magnética en el diagnóstico de Hernia discal tiene superioridad ante la tomografía computarizada y la mielografía, ya que esta no utiliza radiación ionizante y es el estudio más específico para visualizar la anatomía de la columna vertebral para poder detectar lesiones, anomalías o enfermedades que con otros métodos de diagnóstico no son posible ser detectados.
Keywords: HERNIA DISCAL; DIAGNOSTICO DE HERNIA DISCAL; RESONANCIA MAGNETICA EN HERNIA DISCAL